Multilevel rhythms in multimodal communication. (11th October 2021) - Pouw, Wim; Proksch, Shannon; Drijvers, Linda; Gamba, Marco; Holler, Judith; Kello, Christopher; Schaefer, Rebecca S.; Wiggins, Geraint A.
Abstract : It is now widely accepted that the brunt of animal communication is conducted via several modalities, e.g. acoustic and visual, either simultaneously or sequentially. This is a laudable multimodal turn relative to traditional accounts of temporal aspects of animal communication which have focused on a single modality at a time. However, the fields that are currently contributing to the study of multimodal communication are highly varied, and still largely disconnected given their sole focus on a particular level of description or their particular concern with human or non-human animals. Here, we provide an integrative overview of converging findings that show how multimodal processes occurring at neural, bodily, as well as social interactional levels each contribute uniquely to the complex rhythms that characterize communication in human and non-human animals. Though we address findings for each of these levels independently, we conclude that the most important challenge in this field is to identify how processes at these different levels connect. This article is part of the theme issue 'Synchrony and rhythm interaction: from the brain to behavioural ecology'.